Effect of Micro Site Variations on the Phenological Studies of Himalayan Shrubs - Woodfordia, Carissa, Prinsepia and Debregeasia - , Punam; Singh, Balbir; Sharma, Shivesh; , Atul (Indian Forester, 2006)
A phenological study was carried out to know the effect of micro-zonal variations on the different phenophases like flowering, fruiting, seed maturation and seed dispersal etc. of four important multipurpose shrubs of Himachal Himalayas i.e., Woodfordia, Carissa, Prinsepia and Debregeasia species. Flowering phase was enhanced in Woodfordia and Debregeasia species at certain sites due to minute temperature variations.